Khả năng bảo vệ chống ăn mòn thép cacbon của màng sơn epoxy giàu kẽm kết hợp với ống nano cacbon - Vũ, Phạm Gia; Oánh, Vũ Kế; Trúc, Trịnh Anh; Xuân Hằng, Tô Thị (Vietnam Journal of Chemistry, 2015)
The zinc rich epoxy coatings containing cacbonnanotube (CNT) concentrations ranged from 0.5 to 3 % were studied. Morphology of the zinc pigments was examined by scanning electron microscopy (SEM). Mechanical properties as impact and adhesion of the zinc rich epoxy containing CNT were excellent in comparison with zinc rich epoxy. The corrosion protection behaviour of a zinc-rich epoxy coating containing CNT in 3 % NaCl solution was study by Electrochemical Impedance Spectroscopy (EIS) and the salt fog Testing. The EIS results and the Salt Fog testing show that the ability to corrosion protection of the zinc coating has been increased in the presence of 1 % of the CNT.